Reformulasi Etika Perang Menurut Hukum Islam - Rumbaru, Haji Musa (Tasamuh: Jurnal Studi Islam, 2020)
After the Prophet migrated to Madinah, Al-Qur’an began to urge the Muslims of Medina to participate in jihad. Participation includes war and bloodshed, but the root of the word jihad implies more than just of a holy war. Jihad showed undertakings of physical, moral, spiritual, and intellectual. There are many Arabic words that refer to armed combat, such as harb (war), sira’a (assault), who used the Qur’an if war is the main way of the Muslims in performing this effort. Precisely Qur’an chooses words more samara and rich in meaning with a wide range of connotations. Jihad is not one of the pillars of Islam. Jihad is not the main pillars of Islam. Jihad has been and still is an obligation for Muslims to get involved in the struggle in all domains; moral, spiritual, and political, to create a just and civilized society. This paper attempts to explain the problem of the war in the Islamic perspective.